Using passive acoustics to identify a quiet winter foraging refuge for an endangered beluga whale population in Alaska - Castellote, Manuel; Gill, Verena A.; Garner, Christopher D.; Gilstad, Andrea J; Hou, Benjamin X.; Brewer, Arial M.; Knoth, Jessica M. (Frontiers in Marine Science, 2024)
Cook Inlet beluga (CIB), Delphinapterus leucas, have not recovered from subsistence overharvest despite conservation efforts initiated in 2000. Reasons for this lack of recovery are still unclear with anthropogenic noise identified as a high threat in this population's recovery plan. Baseline information on CIB habitat use and soundscape characterization is crucial in evaluating impacts from anthropogenic activities. Using passive acoustic monitoring, we documented the seasonality and foraging occurrence of CIB, together with killer whale (Orcinus orca), harbor porpoise (Phocoena phocoena) and humpback whale (Megaptera novaeangliae), for one year in Chinitna and Tuxedni bays and rivers, two historically important but recently overlooked areas of their critical habitat in western lower Cook Inlet, Alaska. This area's ecological interest converges with planned mining, marine renewable energy, offshore oil and gas production, and commercial shipping. Results revealed higher presence of harbor porpoise, killer whale, and humpback whale in Chinitna compared to Tuxedni but much lower CIB presence. CIB were not detected in Chinitna Bay but were in the river on 21 days September-February and one day in June. However, CIB were never detected feeding in Chinitna River. CIB acoustic crypsis and preferential use of very shallow habitat in Chinitna revealed a perceived predation risk from killer whales. In contrast, CIB were recorded foraging in both Tuxedni Bay and River and were detected September-April on 127 days making it an important winter foraging ground. Low levels of anthropogenic noise disturbance were quantified in both bays making them some of the most undisturbed sections of their critical habitat, but at the same time highly sensitive to further noise disturbance. Commercial shipping was the main noise source likely causing acoustic disturbance to CIB due to communication masking despite current low levels of temporal overlap with beluga presence. We recommend that applicable regulators consider restricting high sound producing anthropogenic activities in and adjacent to Tuxedni Bay from September 1st to May 15th when CIB are actively using this area. Managing future anthropogenic activities to minimize habitat degradation and acoustic disturbance in this winter foraging refuge will be a key component to support the recovery of this endangered population.